Boosting responsivity and speed in 2D material based vertical p-i-n photodiodes with excellent self-powered ability - Maoxin Tian; Yufan Wang; Tianjiao Zhang; Cheng Zhang; Jialei Miao; Zheng Bian; Xiangwei Su; Zongwen Li; Jian Chai; Anran Wang; Fengqiu Wang; Bin Yu; et al. (Nature Communications)
Abstract Vertical p-i-n junctions are key components for optoelectronics to achieve fast response speed. However, a critical bottleneck lies in the complex fabrication techniques and the performance tradeoff between high responsivity and fast speed, especially under self-powered mode. Here, we illustrate the superiority of 2D materials-based vertical p-i-n photodiodes with maximized optical absorption in intrinsic layer (high responsivity), the efficient photocarrier separation (self-power ability), and the high-field drift velocity (fast speed). By optimizing the photocarrier generation/transfer dynamics via doping and thickness engineering, our device with zero voltage bias achieves high built-in electric field, leading to a high responsivity of 0.388 A W−1 and an EQE of 90.5% at 532 nm, a short intrinsic response time of sub-10 ps, a fast switching response time of 23 ns, and a high power conversion efficiency of 6.5%. Our work lays the foundation to resolve the responsivity-speed dilemma without the constraint of lattice mismatch.